Identifying Audience Needs to Effectively Communicate about the Cost of Implementing Sustainable Farming Practices - Kristin E. Gibson; Alexa J Lamm; Kevan W. Lamm (Journal of Applied Communications, 2020)
Water is a complex issue across the globe and is largely affected by a growing world population and higher standard of living. Within the United States, the security of the freshwater supply is an increasing concern and water resource protection may increase if residents are knowledgeable about the issue. Sustainable farming systems will lessen the impact of agriculture on water resources but may cost the end user more to ensure sustainability. Therefore, the purpose of this study was to determine if rural, urban, and suburban audiences differ in their willingness to pay for sustainable farming practices that protect water resources so that communication messages can be tailored. Audience segmentation was used to guide the study. Data were collected with a researcher-developed online survey instrument. The results found water consumers’ overall willingness to pay for more sustainable farming practices was fairly high. Statistically significant differences were found between urban and rural residents’ willingness to pay for sustainable farming practices. Thus, the findings imply residents with differing rurality need tailored communication messages delivered through specific channels.
Keywords: audience segmentation; sustainable farming; water; willingness to pay